2020
DOI: 10.1017/s2045796020000256
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of a new brief scale for subjective personal agency (SPA-5) in people with schizophrenia

Abstract: Aims Personal agency is a variable which potentially facilitates personal recovery in people with serious mental illness. This study aimed to develop a new brief measure for subjective personal agency that can be completed by people with serious mental illness. Methods Two focus group interviews were first conducted with 11 people with schizophrenia to understand the fundamental components of subjective personal agency for people with serious mental illness living in the community. One g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Table 4 summarizes the results. As expected, results showed that the TBS was negatively associated with direct measures of agency assessed in Data Set 4, including the Sense of Agency Scale (SAS; Tapal et al, 2017), r = -.38, p < .001, and the Subjective Personal Agency Scale (Yamaguchi et al, 2020), r = -.40, p < .001. The TBS was positively related to the Avolition scale (Gerritsen et al, 2015), r = .69, p < .001, reflecting difficulties in initiating and persisting in goal-directed activities.…”
Section: Convergent Validitysupporting
confidence: 72%
See 2 more Smart Citations
“…Table 4 summarizes the results. As expected, results showed that the TBS was negatively associated with direct measures of agency assessed in Data Set 4, including the Sense of Agency Scale (SAS; Tapal et al, 2017), r = -.38, p < .001, and the Subjective Personal Agency Scale (Yamaguchi et al, 2020), r = -.40, p < .001. The TBS was positively related to the Avolition scale (Gerritsen et al, 2015), r = .69, p < .001, reflecting difficulties in initiating and persisting in goal-directed activities.…”
Section: Convergent Validitysupporting
confidence: 72%
“…This five-item questionnaire measures personal agency ( Yamaguchi et al, 2020 ). Participants were asked to respond to each item on a Likert-type scale from 1 (=strongly disagree) to 5 (=strongly agree) to items such as “I have an idea of what I want to do and/or how I want to be.” Cronbach’s alpha reliability for the current study was .74.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the Sense of Agency Rating Scale ( Polito et al, 2013 ), which was however designed to measure alterations in general agency beliefs during hypnosis and thus is not suitable to assess cross-situational sense of agency. Another one is the subjective personal agency scale ( Yamaguchi et al, 2020 ), which was however designed to measure sense of agency in people with serious mental disorders, particularly in people suffering from schizophrenia. A further instrument is the sense of agency scale by Asai et al (2009) , which however is published in a Japanese written article and therefore the content of the article, containing not only the items of the scale itself, but also its specific theoretical focus and psychometric properties as well as the methodology used for questionnaire validation is not available for a broad readership.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the understanding of health has shifted from a traditional focus on income and consumption toward a richer multidimensional approach. This shift has been strongly influenced by a body of research in the capabilities' approach, which emphasizes the role of freedom, opportunities, and agency [4,[6][7][8][9][14][15].…”
Section: Introductionmentioning
confidence: 99%